Earthquake supercycles as part of a spectrum of normal fault slip styles. Issue 4 (28th April 2017) - Biemiller, James; Lavier, Luc
Abstract: Like thrust boundaries in subduction zones, some normal faults show evidence of temporally transient slip patterns, such as temporally clustered earthquakes or periods of elevated creep rate. We create rate‐and‐state friction numerical models to assess whether typical distributions of frictional parameters can explain transient slip on normal faults. We constrain our models with geometry from the Wasatch Fault zone, where 5–10 kyr timescale earthquake clusters are recorded on fault scarps. We use numerical models to test whether these earthquake clusters could be the geologic representation of "supercycles" which we define as long‐period stress cycles containing multiple seismic cycles. Field observations, laboratory data, and analogue experiments suggest that the ratio of velocity‐weakening to velocity‐strengthening material varies with the ratio of brittle to ductile material in the shear zone. We therefore employ a linear transition of frictional parameters with depth to simulate bulk frictional properties of the shear zone. We find that for generalized normal faults, rate‐and‐state friction predicts a spectrum of slip behaviors including steady aseismic creep, aseismic transients, clustered earthquakes, and regular seismic cycle earthquakes. The dominant control on slip behavior is the degree of weakening material in the potentially seismogenic fault patch. Earthquake clusters occur with higher proportions of velocity‐weakening material which correspond to more competent, less ductile shear zone assemblages. We find that rate‐and‐state friction predicts a wider spectrum of slip behavior on active normal faults than has been previously recognized, potentially due to geologic preservation and identification issues. Key Points: Rate‐and‐state friction can explain 1‐10 kyr earthquake clusters like those recorded on the Wasatch Fault and the Fucino Fault Rate‐and‐state friction predicts a spectrum of transient normal fault slip behaviors ranging from pure seismic cycle to steady creep Ratio of ductile to brittle material in the shear zone may control normal fault slip style